Structure Optimization of Outlet Uniformity for a Comas Tower Dryer - Liao, Hebin; Zhang, Wei; Borucki, Sebastian; Jiang, Jiasen; Lin, Tianqin; Li, Zhixiong (Frontiers in Energy Research, 2021)
Tobacco drying is an important part in the whole process of cigarette production, and the quality of it is directly related to the quality of cigarettes. CTD (Comas Tower Dryer) is a new type of airflow dryer, which is widely used in tobacco industry because of its high drying efficiency. In actual production, the uneven outlet of tobacco cutter leads to the stacking phenomenon, which affects the subsequent process of production. In this paper, the distribution of internal flow field of drying tower was studied from the aspects of overlap degree of orifice plate and deformation of top structure at the top of the drying tower to explore the way to optimize the inner flow field to lead the uneven distribution of outlet. The results show that the structure whose contact posi-tion between the wall and the outlet extends outward can improve the uniformity of outlet, while the overlap degree of the orifice plate had no effect to the uniformity of outlet.